Understanding Workplace Stress Among Federal Law Enforcement Officers - Sayed, Sarah A. (American journal of criminal justice, 2019)
Research dating back to the 1940s has examined how police work may offer unique and high-volume stressors. While much has been learned from those studies about the sources and consequences of police stress, scholars have typically examined those issues from the perspective of local and state officers. That being the case, much less is known about the sources and consequences of workplace stress among those working at the federal level of law enforcement. To add to this limited knowledge base, here we present findings from 20 in-depth interviews conducted with current federal law enforcement officers in the Southern United States. We provide extensive analysis and description of four key stressors that emerged from the lived experiences of interviewees. This is followed by a discussion of the consequences of these stressors, as well as relevant policy implications.